2017
DOI: 10.3390/epigenomes1030016
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Response to Experimental Demethylation at Seed Germination in the Non-Model Herb Erodium cicutarium

Abstract: Experimental alteration of DNA methylation is a suitable tool to infer the relationship between phenotypic and epigenetic variation in plants. A detailed analysis of the genome-wide effect of demethylating agents, such as 5-azacytidine (5azaC), and zebularine is only available for the model species Arabidopsis thaliana, which suggests that 5azaC may have a slightly larger effect. In this study, global methylation estimates obtained by high-performance liquid chromatography (HPLC) analyses were conducted to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 59 publications
2
24
1
2
Order By: Relevance
“…For the control treatment, the filter paper was moistened with 200 µl of deionized water, and for the demethylation treatment, it was moistened with 200 µl of a 35 µM aqueous solution of the demethylation agent zebularine (Sigma‐Aldrich Corporation, St. Louis, Missouri, USA). The used concentration of zebularine, C 9 H 12 N 2 O 5 , a cytidine analogue, was chosen to be within the range of concentrations used by other studies, where they were shown to be effective without affecting plant survival (see Alonso, Medrano, Pérez, Bazaga, & Herrera, ; Verhoeven & van Gurp, ). Moreover, in a pilot study, we found that a concentration between 25 and 50 µM zebularine visibly slowed plant development, without affecting the viability of the plants (see Figure for images of exemplary gradients of the zebularine trial).…”
Section: Methodsmentioning
confidence: 99%
“…For the control treatment, the filter paper was moistened with 200 µl of deionized water, and for the demethylation treatment, it was moistened with 200 µl of a 35 µM aqueous solution of the demethylation agent zebularine (Sigma‐Aldrich Corporation, St. Louis, Missouri, USA). The used concentration of zebularine, C 9 H 12 N 2 O 5 , a cytidine analogue, was chosen to be within the range of concentrations used by other studies, where they were shown to be effective without affecting plant survival (see Alonso, Medrano, Pérez, Bazaga, & Herrera, ; Verhoeven & van Gurp, ). Moreover, in a pilot study, we found that a concentration between 25 and 50 µM zebularine visibly slowed plant development, without affecting the viability of the plants (see Figure for images of exemplary gradients of the zebularine trial).…”
Section: Methodsmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 11, 2020. ; https://doi.org/10.1101/2020.12.11.421594 doi: bioRxiv preprint superset of the plants considered here. Global methylation may vary within species or individuals in relation to plant age or tissue of origin (Mankessi et al, 2011;Vining et al, 2012;Alonso et al, 2017;Gao et al, 2019), but none of these factors can account for heterogeneous genomic methylation within plants of L. latifolia found here and by , since all DNA samples from the same plant were from even-aged leaf cohorts.…”
Section: Extant Subindividual Epigenetic Heterogeneity and Its Originmentioning
confidence: 75%
“…(2018) for this species showing within-plant heterogeneity in global methylation for a superset of the plants considered here. Global methylation may vary within species or individuals in relation to plant age or tissue of origin (Mankessi et al ., 2011; Vining et al ., 2012; Alonso et al ., 2017; Gao et al ., 2019), but none of these factors can account for heterogeneous genomic methylation within plants of L. latifolia found here and by Alonso et al . (2018), since all DNA samples from the same plant were from even-aged leaf cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental effects induced by variations in DNA methylation have already been largely reported in plants: for example, Baubec et al (2009) showed a reduction in growth after zebularine treatment in Arabidopsis thaliana. Alonso et al (2017) observed a decrease in leaf numbers after treatment with 5-azacytidine, and Tatra et al (2000) reported stem elongation in Stellaria longipes in response to shade by using 5-azacytidine. Our observations are in line with these studies, except that we found a positive effect of hypomethylation on development, such as an increase in leaf and internode numbers.…”
Section: Discussionmentioning
confidence: 99%